Pengaruh Job Demand, Job Crafting, Job Resources Pada Work Engagement - Ihsan Pratama, Fadhiel; Tiarapuspa, Tiarapuspa (Jurnal Etnik: Ekonomi-Teknik, 2023)
The purpose of this study is to analyze the effect of Job demand, Job Crafting, Job Resource on the Work Engagement of employees in manufacturing companies in Surabaya. Data were collected from one hundred and thirty seven employees in Surabaya with the method used in this research is multiple linear regression analysis method. Data analysis used SPSS version 23. The results of testing the hypothesis in this study showed that there was a positive effect of Job demand, Job Crafting, and Job Resources on Work Engagement. Managerial implications in this study are how employees think about the job demands experienced by employees of organizations that have goals, work environment and self-efficacy are very important in group and organizational life. Employees are expected to be able to commit to the organization both emotionally and intellectually. This research is expected to make managers and subsequent researchers think that job demands are supported by many influences on the employees themselves which make the employees enthusiastic in carrying out their duties or obligations